A conceptual framework for the eco-efficiency assessment of small- and medium-sized enterprises. (10th November 2019) - Vásquez, Jenifer; Aguirre, Santiago; Fuquene-Retamoso, Carlos Eduardo; Bruno, Giulia; Priarone, Paolo C.; Settineri, Luca
Abstract: The mitigation and prevention of environmental impacts is still a challenge for most companies, especially for small- and medium-sized enterprises (SMEs). The literature shows that researchers are paying attention to the concept of eco-efficiency, and that companies are making significant efforts to develop sustainable methodologies, as a result of consumer pressure or for government enforcement reasons. However, there is still a lack of concrete initiatives implemented at SME level. The aim of this paper is to present a conceptual framework that may be used to examine to what extent SMEs understand the eco-efficiency concept and implement sustainability strategies. This has been achieved through the identification of the following four specific factors: availability of an environmental management system, environmental knowledge, organizational culture, and environmental monitoring and control. The limitations and research gaps in the specific context have been analyzed, and a conceptual framework that allows the eco-efficiency implementation to be assessed has been proposed. An exploratory study has been carried out on 17 wood industry SMEs from Bogotá, Colombia. The results show that most SMEs are unaware of the existing sustainability strategies and environmental practices. Nevertheless, all the SMEs agreed that the environment requires more attention and they are therefore interested in sustainability strategies to help decrease their negative impact and increase their cost-effectiveness and competitiveness. Graphical abstract: Image 102748 Highlights: A conceptual framework to assess the eco-efficiency level in SMEs is presented. Environmental management strategies and managerial orientations are considered. The framework was applied to examine Colombian SMEs in the wood sector. The results show that efforts to implement sustainability strategies are needed.